Rediscovery and redescription of Silvaseius Barretoae (Yoshida-Shaul and Chant) (Acari : Phytoseiidae) - Demite, Peterson R. [UNESP]; Feres, Reinaldo J. F. [UNESP]; Guanilo, Alberto D.; de Moraes, Gilberto J. (Taylor & Francis Inc, 2008)
New collection records of Silvaseius barretoae (Yoshida-Shaul and Chant) are reported and a redescription of females as well as the first description of male are provided based on specimens collected in Argentina and Brazil.
Keywords: Acari; Phytoseiidae; Galendromimini; Typhlodrominae; predatory mite; Argentina; Brazil